SOCIO-STRUCTURAL INNOVATIONS IN INDONESIA’S URBAN SUFISM: The Case Study of the Majelis Dzikir and Shalawat Nurul Mustafa (JOURNAL OF INDONESIAN ISLAM, 2013)
Sufi tradition has grown significantly in the modern Muslim world, including Indonesia. Currently, Sufism has been not only practiced by villagers, peasants, and non-educated people, but also practiced by urbanites, national elites, and educated people. Moreover, it has experienced significant innovation in terms of its practices and organization. This article takes an in-depth look at the innovationof Sufi tradition socially and structurally in Indonesia. It argues that majelis dzikir and shalawat in Indonesia, like Nurul Mustafa, has represented a new Sufi group that arises out of tarekat group, a group that has been considered as ‘official institution’ in implementing Sufism. The Majelis Nurul Mustafa has strong basis in  urban society, rises from urban majelis taklim, introduces Sufi teaching to its jamā`ah that mostly urban teenagers and youths uses popular methods to attract the interest of those groups to attend its ritual as the complementary of its activity.